Self and meaning in the lives of older people : case studies over twenty years - Coleman, Peter G.; Ivani-Chalian, Christine; Robinson, Maureen (1st ed., 2015)
"More than thirty-five years ago, a longitudinal study was established to research the health and well-being of older people living in an English city. Self and Meaning in the Lives of Older People provides a unique set of portraits of forty members of this group who were interviewed in depth from their later seventies onwards. Focusing on sense of self-esteem and, especially, of continued meaning in life following the loss of a spouse and onset of frailty, this book sensitively illustrates these persons' efforts to maintain independence, to continue to have a sense of belonging and to contribute to the lives of others. It examines both the psychological and the social resources needed to flourish in later life and draws attention to this generation's ability to benefit from strong family support and from belonging to a faith community. In conclusion, it questions whether future generations will be as resilient"--
"Over 35 years ago a longitudinal study was established to research the health and well-being of older people living in an English city. Self and Meaning in the Lives of Older People provides a unique set of portraits of forty members of this group who were interviewed in depth from their later 70s onwards. Focusing on sense of self-esteem and, especially, of continued meaning in life following the loss of a spouse and onset of frailty, this book sensitively illustrates these persons efforts to maintain independence, to continue to have a sense of belonging and to contribute to the lives of others. It examines both the psychological and social resources needed in order to flourish in later life and draws attention to this generation's ability to benefit from strong family support as well as from belonging to a faith community. In conclusion it questions whether future generations will be as resilient"--
Machine generated contents note: 1. Living a long life: why survive?; 2. From self-esteem to meaning: studying psychological well-being in later life; 3. Investigating older people's lives at the end of the twentieth century; 4. Ageing together; 5. Adaptation to loss of spouse; 6. Ageing alone; 7. Women becoming frailer; 8. Men becoming frailer; 9. Towards one hundred years; 10. The future of later life: personal and policy perspectives on ageing and meaning.
Includes bibliographical references (pages 239 -242) and index.
Includes bibliographical references and index.
Keywords: Older people -- Psychology; Self-perception in old age; Aging -- Psychological aspects -- Case studies; Meaning (Psychology)